Institutional rules and biased rule enforcement - Simon Columbus; Lars P. Feld; Matthias Kasper; Matthew D. Rablen (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2025)
This study investigates how institutional rules and fairness in enforcement affect cooperation and compliance in heterogenous groups. In a preregistered online experiment (n = 1, 254), we vary both the existence of a rule governing contributions to a public good as well as whether enforcement of the rule is biased against some players. We find that merely stating a rule has a stronger effect on behaviour than rule enforcement. Specifically, institutional rules promote cooperation by strengthening personal and social norms, which in turn sustains contributions over time. In contrast, in the absence of a rule, norms are weaker and contributions decline. Fair rule enforcement reduces free-riding and increases compliance, but it also crowds out full cooperation. Finally, we find no evidence that biased rule enforcement erodes norms, reduces cooperation, or diminishes rule compliance. Our findings highlight the crucial role of institutional rules in strengthening norms and sustaining cooperation in heterogeneous groups, even in the absence of enforcement or when rule enforcement is biased.
Keywords: H41; C72; C91; C92; 330; public goods; rule compliance; rule enforcement; social norms